The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.3201/eid1304.061316
|View full text |Cite
|
Sign up to set email alerts
|

Global Distribution of Panton-Valentine Leukocidin–positive Methicillin-resistantStaphylococcus aureus,2006

Abstract: Some formerly continent-specific clones have now spread around the world

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
296
3
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(330 citation statements)
references
References 40 publications
22
296
3
7
Order By: Relevance
“…Among these, SCCmec IV and V elements were found in 30 (71.4 %) and 12 (28.6 %) isolates, respectively; no other SCCmec element was found in this collection (Table 1). This is in accordance with other reports (Tristan et al, 2007;Boyle-Vavra & Daum, 2007) that pvl carriage is much more frequently associated with SCCmec types IV and V than other types (I, II or III) in S. aureus. In Hong Kong, pvl-positive SCCmec type V isolates have been reported in five MRSA strains (Ho et al, 2007).…”
Section: Jmm Correspondencesupporting
confidence: 93%
See 1 more Smart Citation
“…Among these, SCCmec IV and V elements were found in 30 (71.4 %) and 12 (28.6 %) isolates, respectively; no other SCCmec element was found in this collection (Table 1). This is in accordance with other reports (Tristan et al, 2007;Boyle-Vavra & Daum, 2007) that pvl carriage is much more frequently associated with SCCmec types IV and V than other types (I, II or III) in S. aureus. In Hong Kong, pvl-positive SCCmec type V isolates have been reported in five MRSA strains (Ho et al, 2007).…”
Section: Jmm Correspondencesupporting
confidence: 93%
“…Since the 1990s, community-associated (CA)-MRSA infections have shown a steady increase, and are becoming a significant public-health concern. PVLpositive MRSA isolates have been shown to have distinct genetic backgrounds in different areas, for instance, multilocus sequence typing (MLST) types ST80, ST8 and ST59 were found in the major clones in Europe, USA and Taiwan, respectively (Vandenesch et al, 2003;Tristan et al, 2007;Chen et al, 2005).…”
Section: Jmm Correspondencementioning
confidence: 99%
“…In Germany, the prevalence of MRSA isolates among HCWs was 11.3%, among which 9.1% of the isolates were positive for PVL (18). Worldwide, there is an increase in the spread of PVL-positive MRSA clones (19). The current study found that the prevalence of pvl gene, MSSA-PVL and MRSA-PVL isolates were 16.9%, 6.8% and 10.1 % respectively.…”
Section: Discussionmentioning
confidence: 45%
“…Most of the PVL-positive CA-MRSA isolates are multidrug resistant strains and they carry the smallest SCCmec elements (either SCCmec type IV or SCCmec type V) (Tristan et al, 2007). In fact, the distribution of PVL-positive MRSA is worldwide.…”
Section: Antibiotic Susceptibilities Of the Strainsmentioning
confidence: 99%
“…In fact, the distribution of PVL-positive MRSA is worldwide. Due to intercontinental exchanges, several PVL-positive CA-MRSA clones (e.g., ST8 clone (USA300), ST1 clone (USA400), ST59 clone (USA1000), ST80 clone and ST30 clone) have spread to other continents which were previously present (Tristan et al, 2007).…”
Section: Antibiotic Susceptibilities Of the Strainsmentioning
confidence: 99%